2022
DOI: 10.1126/sciadv.abo4158
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into G protein activation by D1 dopamine receptor

Abstract: G protein–coupled receptors (GPCRs) comprise the largest family of membrane receptors and are the most important drug targets. An agonist-bound GPCR engages heterotrimeric G proteins and triggers the exchange of guanosine diphosphate (GDP) with guanosine triphosphate (GTP) to promote G protein activation. A complete understanding of molecular mechanisms of G protein activation has been hindered by a lack of structural information of GPCR–G protein complex in nucleotide-bound states. Here, we report the cryo-EM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 58 publications
(86 reference statements)
3
19
0
Order By: Relevance
“…Lastly, DRD1 titration with dopamine and fenoldopam produced EC50 values of 2.6 µM and 145 nM, respectively ( Figure 2C ) that correspond well with the reported EC50 values. 38,39 DRD1 titration with antagonist SCH 23390 in the presence of 10 µM agonist dopamine yielded an IC50 of 26 nM, which also agrees with the reported value. 40 Overall, these characterizations demonstrate that the GPCR in IGNiTR maintains function comparable to live cell assays and IGNiTR can differentiate among various ligand efficacies.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Lastly, DRD1 titration with dopamine and fenoldopam produced EC50 values of 2.6 µM and 145 nM, respectively ( Figure 2C ) that correspond well with the reported EC50 values. 38,39 DRD1 titration with antagonist SCH 23390 in the presence of 10 µM agonist dopamine yielded an IC50 of 26 nM, which also agrees with the reported value. 40 Overall, these characterizations demonstrate that the GPCR in IGNiTR maintains function comparable to live cell assays and IGNiTR can differentiate among various ligand efficacies.…”
Section: Resultssupporting
confidence: 90%
“…The full agonist dopamine produced higher DDR than the partial agonist fenoldopam at saturated concentrations, with both producing a DDR > 1. The result validates that both full and partial agonists induce the active conformational state 38,39 and that IGNiTR can differentiate ligand efficacies. DRD1 antagonist, SCH 23390, does not increase luminescence compared to the no drug condition.…”
Section: Resultssupporting
confidence: 74%
“…2A), strong forces at the air-water interface led to the dissociation of the complex during cryo–electron microscopy (cryo-EM) grid preparation, resulting in heterogeneous particles and impeding structure determination. To enhance complex stability, we take advantage of the fusion protein strategy ( 42 ), where the N terminus of Gγ 1 is fused to the C terminus of KCTD5 (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…As a result of these conformational changes, G s is closer to TM5 than G q , highlighting the important role of TM5 in determining G s selectivity. Indeed, TM5 in most G s -coupled receptors has a C-terminal helical extension, and previous studies have shown that the A/V 5.65 Q 5.68 Φ 5.69 (Φ represents hydrophobic residues) motif in TM5 is prevalent in receptors that exclusively couples to G s and is critical for G s coupling in D1R ( 46 , 47 ). Residues at position 5.65 in G s -coupled receptors prefer hydrophobic residues with small side chains such as alanine and valine because of their close distance from the hydrophobic pocket formed by L(−1), L(−2), and L(−7) in Gα s ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6 C ). Mutation of A 5.65 in leucine would cause a clash with this pocket and impairs the G s coupling ( 47 ). In contrast, leucine is dominant at position 5.65 in G q -coupled receptors, due to its long distance from the hydrophobic pocket formed by V(−1), L(−2), and L(−7) in Gα q ( Fig.…”
Section: Resultsmentioning
confidence: 99%